The modulation of enzyme indoleamine 2,3-dioxygenase from dendritic cells for the treatment of type 1 diabetes mellitus - Abram, Débora Moitinho; Fernandes, Luis Gustavo Romani; Ramos Filho, Antônio Celso Saragossa; Simioni, Patrícia Ucelli [UNESP] (Taylor & Francis, 2017)
Diabetes mellitus type 1 (DM1) is an autoimmune disease in which β-cells of the pancreas islet are destroyed by T lymphocytes. Specific T cells are activated by antigen-presenting cells, mainly dendritic cells (DCs). It is already known that the regulation of tryptophan pathway in DC can be a mechanism of immunomodulation. The enzyme indoleamine 2,3-dioxygenase (IDO) is present in many cells, including DC, and participates in the metabolism of the amino acid tryptophan. Recent studies suggest the involvement of IDO in the modulation of immune response, which became more evident after the in vitro demonstration of IDO production by DC and of the ability of these cells to inhibit lymphocyte function through the control of tryptophan metabolism. Current studies on immunotherapies describe the use of DC and IDO to control the progression of the immune response that triggers DM1. The initial results obtained are promising and indicate the possibility of developing therapies for the treatment or prevention of the DM1. Clinical trials using these cells in DM1 patients represent an interesting alternative treatment. However, clinical trials are still in the initial phase and a robust group of assays is necessary.
Keywords: Autoimmunity; Clinical trials; Dendritic cells; Diabetes mellitus type 1; Immunoregulation; Indoleamine; Tolerance; Tryptophan